2021 European Guideline on the management of proctitis, proctocolitis and enteritis caused by sexually transmissible pathogens. (31st May 2021) - de Vries, H.J.C.; Nori, A.V.; Kiellberg Larsen, H.; Kreuter, A.; Padovese, V.; Pallawela, S.; Vall‐Mayans, M.; Ross, J
Abstract: This guideline intents to offer guidance on the diagnosis and management of patients with gastrointestinal symptoms and a suspected sexually transmitted cause. Proctitis is defined as an inflammatory syndrome of the anal canal and/or the rectum. Infectious proctitis can be sexually transmitted via genital–anal mucosal contact, but some also via digital contact and toys. Neisseria gonorrhoeae, Chlamydia trachomatis (including lymphogranuloma venereum), Treponema pallidum and herpes simplex virus are the most common sexually transmitted anorectal pathogens. Shigellosis can be transferred via oral–anal contact and may lead to proctocolitis or enteritis. Although most studies on these infections have concentrated on men who have sex with men (MSM), women having anal intercourse may also be at risk. A presumptive clinical diagnosis of proctitis can be made when there are symptoms and signs, and a definitive diagnosis when the results of laboratory tests are available. The symptoms of proctitis include anorectal itching, pain, tenesmus, bleeding, constipation and discharge in and around the anal canal. The majority of rectal chlamydia and gonococcal infections are asymptomatic and can only be detected by laboratory tests. Therefore, especially when there is a history of receptive anal contact, exclusion of anorectal infections is generally indicated as part of standard screening for sexually transmitted infections (STIs). Condom use does not guarantee protection from STIs, which are often spread without penile penetration. New in this updated guideline is: (i) lymphogranuloma venereum proctitis is increasingly found in HIV‐negative MSM, (ii) anorectal Mycoplasma genitalium infection should be considered in patients with symptomatic proctitis after exclusion of other common causations such N. gonorrhoeae, C. trachomatis, syphilis and herpes, (iii) intestinal spirochetosis incidentally found in colonic biopsies should not be confused with syphilis, and (iv) traumatic causes of proctitis should be considered in sexually active patients.